Corporate Social Responsibility and Financial Performance in Shariah Banks: A Review - Umi & Umi Nandiroh (ITB AAS INDONESIA Surakarta, 2023)
This review explores the relationship between Corporate Social Responsibility (CSR) and financial performance in Shariah banks. Shariah banks, operating under Islamic principles, face unique challenges and opportunities in integrating CSR into their operations. The essay reviews empirical research on the correlation between CSR initiatives and financial performance in Shariah banks, highlighting studies indicating a positive relationship, potential benefits, and stakeholder satisfaction. Counterarguments and conflicting findings are also addressed, acknowledging challenges and limitations. The review discusses the reputational advantages of CSR, including enhanced brand image, customer loyalty, and attraction of socially responsible investors. Moreover, it explores how CSR initiatives align with Islamic values, strengthening the bank's position within the Muslim community. The essay further delves into the challenges faced by Shariah banks in implementing CSR, ensuring compliance with Islamic principles while meeting regulatory requirements. It also addresses potential conflicts between CSR practices and financial goals, emphasizing the need for careful balance and alignment. Lastly, the review explores resource constraints and cost considerations for smaller Shariah banks and proposes strategies for overcoming these challenges. Overall, this review provides a comprehensive analysis of the relationship between CSR and financial performance in Shariah banks, offering insights into the significance and implications of CSR integration in the Islamic finance industry.